Pengaruh Konflik Pekerjaan-Keluarga Terhadap Kepuasan Kerja (Kasus Karyawan Bank BJB Cabang Utama Bandung) - Afina Azka Yasyifa; Sri Raharso (Jurnal Riset Bisnis dan Investasi, 2018)
The current business organization is important to review the conflict between work and family. It can impact on the survival of employees in business organizations. Work-family conflicts can be one reason employee dissatisfaction with work. The relationship between work-family conflict and job satisfaction. Based on research conducted on 118 respondents employees Bank Bjb Office Main Branch Bandung obtained results that show there is a relationship between work family conflict with job satisfaction. This is evidenced by the results of correlation analysis between work family conflict variables with job satisfaction included in the negative and significant relationship. Furthermore, work family conflict also has a negative effect on job satisfaction in the regression analysis done.